A Preliminary Study on the Correlation Between Age and Endometrial Receptivity - Guo S; Zhang D; Zhao S; Zhang H; Sun Y; Yan L (Dove Medical Press, 2023)
Song Guo,1,* Di Zhang,2,* Shan Zhao,1 Huan Zhang,1 Yijuan Sun,3 Li Yan1 1Gynecology Department, The First Affiliated Hospital of Shandong First Medical University, Jinan, Shandong Province, People's Republic of China; 2Obstetrics Department, Shandong Provincial Third Hospital, Jinan, Shandong Province, People's Republic of China; 3Shanghai Ji Ai Genetics & In vitro Fertilization Institute, Obstetrics and Gynecology Hospital, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Yijuan Sun, Shanghai Ji Ai Genetics & IVF Institute, Obstetrics and Gynecology Hospital, Fudan University, NO. 352 Dalin Road, Shanghai, 200011, People's Republic of China, Tel +86-21-6345-5468, Fax +86-21-33180478, Email xiaowei2987415@163.com Li Yan, Gynecology Department, The First Affiliated Hospital of Shandong First Medical University, No. 16766 Jingshi Road, Jinan, 250014, Shandong Province, People's Republic of China, Tel +86-531-89268763, Fax +86-531-82963647, Email yanliqy@163.comBackground: It is well established that female fertility declines with age, primarily because of loss of ovarian function. However, few studies have clarified the relationship between increasing age and endometrial receptivity. Here, we aimed to study the impact of age on endometrial receptivity, meanwhile, we examined the expression of endometrial mesenchymal stem cell (eMSC) surface markers (CD146 and PDGF-Rβ), essential for endometrial development and re-growth, in different age groups.Methods: Participants were enrolled in this study between October 2020 and July 2021. All 31 patients were divided into three age groups; early (30- 39 years old, n=10), intermediate (40- 49 years old, n=12) and advanced (≥ 50 years old, n=9). We assessed localization and expression of CD146 and PDGF-Rβ by immunofluorescence and further analyzed selected endometrial receptivity markers (Homeobox A10 HOXA10, leukemia inhibitory factor LIF and osteopontin) and steroid hormone receptors by immunohistochemistry.Results: There were no significant differences in expression of HOXA10 and OPN (p> 0.05) among the three groups. However, we found a significant difference in LIF expression between the early and advanced age groups, with higher expression noted in the latter group (p=0.02). Similarly, estrogen receptor (ER) and progesterone receptor (PR) expression were significantly increased (p=0.01 and p=0.01, respectively) in the advanced age group compared with the early age group. There were no significant difference in CD146 and PDGF-Rβ expression among the three groups (p> 0.05).Conclusion: These results suggest that the age of the patient does not influence their endometrial receptivity. So, this study serves to increase our understanding of the impact of age and eMSCs on endometrial receptivity and expands the etiology of age-related infertility.Keywords: age, endometrial receptivity, endometrial mesenchymal stem cells